Factors Associated with Random Blood Glucose Status among Type 2 Diabetes Patients: A Cross-Sectional Study at Alianyang Health Center, Pontianak - Novia Suryaningsih; Marlenywati; Iskandar Arfan (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2025)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to insulin resistance and impaired insulin secretion. Prevention and management of type 2 diabetes require health education, dietary regulation, regular physical activity, and adherence to medication. This study aimed to identify factors associated with random blood glucose levels in patients with type 2 diabetes mellitus in Pontianak City. This quantitative study employed a cross-sectional design. The sample consisted of 93 patients with diabetes mellitus who visited Alianyang Health Center in Pontianak City. Data were analyzed using the Chi-Square test. The results showed a significant relationship between body mass index (p = 0.006), family history (p = 0.001), and exercise or physical activity (p = 0.003) with random blood glucose levels among patients at Alianyang Health Center. These findings indicate that both biological and lifestyle factors play an important role in blood glucose control. Patients are encouraged to maintain an ideal body mass index, engage in regular physical activity, and adopt healthy lifestyle behaviors. In addition, individuals with a family history of diabetes require early screening and continuous monitoring to prevent complications and improve glycemic control.Diabetes melitus merupakan penyakit metabolik kronis yang ditandai oleh hiperglikemia akibat resistensi insulin dan gangguan sekresi insulin. Pencegahan dan pengelolaan diabetes melitus tipe 2 memerlukan edukasi kesehatan, pengaturan pola makan, aktivitas fisik yang teratur, serta kepatuhan terhadap pengobatan. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang berhubungan dengan kadar glukosa darah sewaktu pada pasien diabetes melitus tipe 2 di Kota Pontianak. Penelitian ini merupakan penelitian kuantitatif dengan desain cross-sectional. Sampel penelitian berjumlah 93 pasien diabetes melitus yang berkunjung ke Puskesmas Alianyang Kota Pontianak. Data dianalisis menggunakan uji Chi-Square. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara indeks massa tubuh (p = 0,006), riwayat keluarga (p = 0,001), dan aktivitas fisik atau olahraga (p = 0,003) dengan kadar glukosa darah sewaktu pada pasien di Puskesmas Alianyang. Temuan ini menunjukkan bahwa faktor biologis dan gaya hidup memiliki peran penting dalam pengendalian kadar glukosa darah. Pasien dianjurkan untuk menjaga indeks massa tubuh yang ideal, melakukan aktivitas fisik secara teratur, serta menerapkan pola hidup sehat. Selain itu, individu dengan riwayat keluarga diabetes perlu melakukan skrining dini dan pemantauan berkala untuk mencegah komplikasi serta meningkatkan pengendalian glikemik.